2012
DOI: 10.1002/ece3.269
|View full text |Cite
|
Sign up to set email alerts
|

Hiding deep in the trees: discovery of divergent mitochondrial lineages in Malagasy chameleons of the Calumma nasutum group

Abstract: We conducted a comprehensive molecular phylogenetic study for a group of chameleons from Madagascar (Chamaeleonidae: Calumma nasutum group, comprising seven nominal species) to examine the genetic and species diversity in this widespread genus. Based on DNA sequences of the mitochondrial gene (ND2) from 215 specimens, we reconstructed the phylogeny using a Bayesian approach. Our results show deep divergences among several unnamed mitochondrial lineages that are difficult to identify morphologically. We evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 35 publications
2
25
1
Order By: Relevance
“…However, many recent studies of savanna and grassland lineages, especially in Australia, emphasize that unrecognized, but biogeographically significant lineages remain overlooked (e.g. Agarwal & Ramakrishnan, ; Domingos et al., ; Gehring et al., ; Guarnizo et al., ; Oliver, Couper, et al., ). This includes both distinctive relict taxa with restricted ranges such as O. murrumanu (discovered and described as part of this work), and divergent lineages that remain confounded in widespread and diverse species complexes such as O. gracilis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many recent studies of savanna and grassland lineages, especially in Australia, emphasize that unrecognized, but biogeographically significant lineages remain overlooked (e.g. Agarwal & Ramakrishnan, ; Domingos et al., ; Gehring et al., ; Guarnizo et al., ; Oliver, Couper, et al., ). This includes both distinctive relict taxa with restricted ranges such as O. murrumanu (discovered and described as part of this work), and divergent lineages that remain confounded in widespread and diverse species complexes such as O. gracilis .…”
Section: Discussionmentioning
confidence: 99%
“…Larger ranges and evidence of introgression suggest a more dynamic history of the boundary between the AMT and AAZ. Resolving unrecognized biological diversity in savannas (Gehring et al., ; Miraldo et al., ; Werneck et al., ) is essential for understanding the history of these poorly known biomes.…”
Section: Discussionmentioning
confidence: 99%
“…Given the high molecular variation found especially within T. gravenhorstii (Boumans et al 2007) it might be suspected that they represent species complexes, as has been observed with other widespread Malagasy reptiles thought to occur over different ecoregions in Madagascar (e.g., Raxworthy & Nussbaum 2006;Raxworthy et al 2007;Rocha et al 2010;Florio et al 2012;Gehring et al 2012aGehring et al , 2012b.…”
Section: Introductionmentioning
confidence: 86%
“…In our first approach, the topology obtained from the Bayesian analysis of the concatenated mtDNA sequences only (not including redundant identical sequences of same haplotypes) was used as a guide for manually grouping taxa at different levels by searching for the threshold at which the intraclade p ‐distances in the mtDNA sequences were lower than the interclade p ‐distances (Gehring et al ., ). This approach (pDist approach) was performed using net p ‐distances as estimated in MEGA5 (Tamura et al ., ).…”
Section: Methodsmentioning
confidence: 97%